An Easy and Efficient Method for the Synthesis of Quinoxalines Using Recyclable and Heterogeneous Nanomagnetic‐Supported Acid Catalyst under Solvent‐Free Condition. Issue 18 (14th May 2018) - Harsha, Kachigere B.; Rangappa, Shobith; Preetham, Habbanakuppe D.; Swaroop, Toreshettahally R.; Gilandoust, Maryam; Rakesh, Kodgahally S.; Rangappa, Kanchugarakoppal S.
Abstract: Synthesis of quinoxalines from o ‐phenylenediamines ( o ‐PDs) with electronically diversified 1, 2‐diketones and α‐bromoketones via simple cyclocondensation reaction using an heterogeneous nano‐ϒ‐Fe2 O3 ‐SO3 H catalyst has been reported under solvent free condition. Low cost, easy workup, high yield, operational simplicity, less reaction time, environmentally benign nature and catalyst is magnetically retrievable and can be reused up to five catalytic cycles without significant loss in the product yields are the noteworthy features of this protocol. Abstract : Synthesis of functionalised quinoxalines from o ‐phenylenediamines ( o ‐PDs) and electronically diversified 1, 2‐diketones and α‐bromoketones via simple cyclocondensation reactions under solvent free condition by using magnetically retrievable nano‐ϒ‐Fe2 O3 ‐SO3 H catalyst has been reported. Low cost, easy workup, high yield, operational simplicity, less reaction time, environmentally benign nature are the noteworthy features of this protocol.